Atividade antifúngica de óleos essenciais de citros no controle do bolor verde (Penicillium digitatum sacc.) e bolor azul (Penicillium italicum wehmer) - Bedo, Ana Carolina Vidotte (Universidade Federal de São Carlos, 2025)
Green and blue molds, caused respectively by the fungi Penicillium digitatum and Penicillium italicum, represent significant issues in citrus farming due to their ability to cause considerable postharvest losses and compromise the commercial quality of fruits. This study aimed to evaluate the antifungal activity of essential oils (EOs) extracted from different citrus genotypes in the control of these phytopathogens. EOs from Amber, Eureka, Harvey, and Siciliano lemons, Pêra Rio IAC sweet orange, and Late IAC 585 mandarin were used, as well as commercial EOs from orange and lemon, both provided by Cisol. In the in vitro experiment, the disc diffusion method was applied to assess the inhibition of mycelial growth of P. digitatum and P. italicum by the EOs. The experiment followed a completely randomized design (CRD), with five replicates, in an 8 × 6 factorial scheme, consisting of eight types of EOs and five concentrations (0; 2,5; 7,5; 12,5; 17,5 and 100%). In the in vivo test, the effectiveness of EOs in controlling P. italicum was evaluated in Tahiti acid lime fruits. The fruits were inoculated 24 hours before (preventive method) and 24 hours after (curative method) EO treatment. The experiment was carried out in a CRD, in a 2 × 2 × 3 + 2 factorial scheme, with three replicates, including two control methods (preventive and curative), three EO types (from Pêra Rio orange, Harvey lemon, and commercial lemon), three concentrations (0; 12,5 and 17,5%), and a positive control (Imazalil) and negative control (water). The results showed that the EOs were not effective against P. digitatum, as the inhibition zones were similar to those of the negative control (water only). However, for P. italicum, the pure EOs from Eureka, Late IAC 585, and commercial lemon exhibited higher inhibition than the chemical control. In Tahiti lime fruit treatment, the curative approach at 17,5% was more efficient, reducing disease incidence and severity. The results indicate that EO effectiveness depends on the genotype, concentration, and application strategy, with the curative method being the most promising for the postharvest control of P. italicum.
Antifungal activity of citrus essential oils in the control of green mold (Penicillium digitatum Sacc.) and blue mold (Penicillium italicum Wehmer)
Keywords: Pós-colheita; Lima ácida Tahiti; Controle alternativo; Post-harvest; Tahiti acid lime; Alternative control; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA